1990
DOI: 10.1149/1.2086293
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prior Cathodic Polarization on the Initiation of Pitting on Aluminum

Abstract: Prior cathodic polarization was found to increase pit densities on aluminum by a factor of 100 during the first 20 ms of anodic polarization above the pit initiation potential, in 1N HC1 at 65~ Enhancements of the average pit growth current densities were also observed. Immersion of aluminum in solutions of HC1, or NaOH followed by HC1, before cathodic polarization, was also necessary to obtain cathodic enhancement of pitting. The total pit volume at 20 ms was approximately the faradaic equivalent volume of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
0
20
2
Order By: Relevance
“…This is immediately evident for the dc process from the tunnel structures that result. 8,11,13 The growth rates we calculate are much greater than the ones reported for those investigations. For both processes, the steady-state dissolution potential is the repassivation potential, because this is the only potential at which both passivation and dissolution can occur.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…This is immediately evident for the dc process from the tunnel structures that result. 8,11,13 The growth rates we calculate are much greater than the ones reported for those investigations. For both processes, the steady-state dissolution potential is the repassivation potential, because this is the only potential at which both passivation and dissolution can occur.…”
contrasting
confidence: 65%
“…The ac etch process operates near room temperature, whereas the dc process is run at temperatures above 65°C. Hebert and Lin 11 found that prior cathodic polarization enhances early pit nucleation and reduces the size of the potential transient. This is immediately evident for the dc process from the tunnel structures that result.…”
mentioning
confidence: 99%
“…2, the stationary anodic currents are plotted on a logarithmic scale vs. the corrected potential, which was obtained by subtracting lo and iR3 from the applied potential. In terms of the electrical model, the corrected potential here is 4)2 + Vr -0.27 V. The linear relation between log i and the corrected potential in the figure ( aF c= exP_-__1oJ-exPI--i-iioJj [5] [6]…”
Section: Resultsmentioning
confidence: 99%
“…The electrograining procedure involves cycling of the potential of the alloy, such that anodic film formation followed by pitting occurs under anodic potentials and hydrogen evolution, with associated deposition of hydrated alumina, under cathodic potentials . The cathodic polarization has an important role in ensuring uniformity of pitting during the anodic part of the cycle . The resultant plate has a convoluted surface that is desired for its water retentive property and the adhesion of a photosensitive coating .…”
Section: Introductionmentioning
confidence: 99%